Circulating miRNAs as Novel Diagnostic Biomarkers in Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis. (20th August 2019) - Cai, Changzhou; Lin, Yiming; Yu, Chaohui
Abstract : Background and Aims . Recent studies have indicated that circulating miRNAs could serve as accurate biomarkers for diagnosing nonalcoholic fatty liver disease (NAFLD). We aimed to assess the evidence on the probability of circulating miRNAs as new diagnostic biomarkers in patients with NAFLD. Methods . We comprehensively retrieved relevant English literature from the databases of PubMed, Embase, and the Cochrane Library from 2000 to 1 January 2019. The diagnostic accuracy of circulating miRNAs as markers for NAFLD was analyzed. Moreover, we evaluated the methodological quality of the included article. STATA was applied to perform statistical analyses. Results . In this meta-analysis, 17 studies that enrolled 1408 patients of NAFLD and 926 healthy people from 6 articles were analyzed. We constructed a summary receiver-operating characteristic (SROC) curve of all circulating miRNAs, and the area under the curve (AUC) was 0.83, with the pooled sensitivity (SEN) 0.70 and the pooled specificity (SPE) 0.82 in distinguishing patients with NAFLD from healthy controls. Among them, miR-122 showed high diagnostic accuracy, with the diagnostic index of pooled SEN, SPE, and AUC being 0.88, 0.66, and 0.86, respectively. We then performed subgroup analyses based on the mode of miRNA regulation, countries, miRNA profiling, sample size, and male proportion. We then did a regression analysis and found the cause of heterogeneity might be miRNA profiling. Finally, publication bias was not found, and Fagan's nomogram showed valuable clinical utility. Conclusion . Circulating miRNAs, especially miR-122, might be promising diagnostic biomarkers for NAFLD with high-accuracy, and more large-sample studies are required to support the above findings in the future.